The Information Revolution in Asia - Hachigian, Nina (RAND Corporation, 2003)
This report discusses the information revolution in the Asia-Pacific region and its likely course over the next five to ten years. Key questions addressed in this report include the extent to which the information revolution has taken hold of markets in this region, the political implications of the information revolution for Asian governments, the variations between individual countries, and the prospects for further information-technology-related developments in the region.